Association between Dyslipidaemia and Sensorineural Hearing Loss: A Cross-sectional Study - Megha Doiphode; Gundappa D Mahajan; Vinod V Shinde; Mayur Ingale (Journal of Clinical and Diagnostic Research)
Introduction: Sensorineural Hearing Loss (SNHL) is a common condition with various causes, including issues related to blood flow and metabolism. Recent studies have suggested a possible association between abnormal blood lipid levels and SNHL. Aim: To assess the association between sensorineural hearing loss and fasting lipid profiles. Materials and Methods: This cross-sectional study was conducted at Dr. D. Y. Patil Medical College, Pimpri, Pune, Maharashtra, India, from April 1, 2023, to October 30, 2024. It included 38 patients with SNHL and 38 age- and sex-matched patients without hearing loss. Fasting lipid levels, including Total Cholesterol (TC), Low-Density Lipoprotein (LDL), Very Low-Density Lipoprotein (VLDL), High-Density Lipoprotein (HDL), and Triglycerides (TG), were measured in both groups. Pure Tone Audiometry (PTA) was employed to assess the degree of hearing loss. Data were analysed using Chi-square and t-tests, with p-values <0.05 considered statistically significant. Results: The mean age of participants was comparable between groups, with the SNHL group having a mean age of 52.6±11.4 years and the control group having a mean age of 51.9±10.8 years. The cases had significantly higher mean TC (215.4±32.7 mg/dL), LDL (138.2±24.5 mg/dL), and TG (175.6±40.2 mg/dL) compared to controls. HDL levels were significantly lower in cases (36.8±6.9 mg/dL) compared to controls (44.1±5.8 mg/dL). Additionally, 73.7% (n=28) of cases had HDL <40 mg/dL compared to 21% (n=8) in controls. Dyslipidaemia was significantly associated with increased hearing thresholds across all tested frequencies. Conclusion: Dyslipidaemia was significantly associated with SNHL, suggesting the importance of monitoring lipid profiles in at-risk individuals. Early intervention may help prevent or mitigate hearing loss.